2015
DOI: 10.1038/ncomms8146
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex associations of ankylosing spondylitis are complex and involve further epistasis with ERAP1

Abstract: Ankylosing spondylitis (AS) is a common, highly heritable, inflammatory arthritis for which HLA-B*27 is the major genetic risk factor, although its role in the aetiology of AS remains elusive. To better understand the genetic basis of the MHC susceptibility loci, we genotyped 7,264 MHC SNPs in 22,647 AS cases and controls of European descent. We impute SNPs, classical HLA alleles and amino acid residues within HLA proteins, and tested these for association to AS status. Here we show that in addition to effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
226
4
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 242 publications
(256 citation statements)
references
References 46 publications
19
226
4
7
Order By: Relevance
“…No significant difference was observed between the frequencies of B*27 subtypes in HLA-B27-positive populations (AS patients and controls). When we compared all patients with AS to controls who were B*27-negative, we observed results similar to those found in Cortes, et al 4 When we analyzed only B27-positive patients with AS and B27-positive control subjects, all these differences disappeared. However, the HLA-B*40:01 allele was significantly increased in B*27-positive patients with AS compared with B*27-positive controls (P BONF < 0.001, OR 23.36, 95% CI 3.04-179.42).…”
Section: To the Editorsupporting
confidence: 75%
“…No significant difference was observed between the frequencies of B*27 subtypes in HLA-B27-positive populations (AS patients and controls). When we compared all patients with AS to controls who were B*27-negative, we observed results similar to those found in Cortes, et al 4 When we analyzed only B27-positive patients with AS and B27-positive control subjects, all these differences disappeared. However, the HLA-B*40:01 allele was significantly increased in B*27-positive patients with AS compared with B*27-positive controls (P BONF < 0.001, OR 23.36, 95% CI 3.04-179.42).…”
Section: To the Editorsupporting
confidence: 75%
“…One replicable example of epistatic interaction is the ERAP1-HLA interaction for psoriasis (MIM: 177900) and ankylosing spondylitis (MIM: 106300). 54 The Utility of GWAS-Derived Genetic Predictors In 2007, it was shown that one could use GWAS data from human studies to create genetic predictors for disease and other complex traits by estimating the effect size at multiple loci in a discovery sample and using those estimated SNP effects in independent samples 13,55 to generate a polygenic risk score (PRS) per individual. A thorough review of different methods of generating PRSs is outside the scope of this review, but currently the key driving force influencing prediction accuracy is the size of the discovery sample used for estimating the effects of individual variants.…”
Section: Pleiotropy Is Pervasivementioning
confidence: 99%
“…ERAP1 haplotypes were also imputed in 4,230 unrelated AS cases and 9,700 unrelated, ethnically matched controls from the IGAS Immunochip study as previously described (1,9). At the ERAP1 locus (chr5:96104000-96190000; HG19 coordinates), 320 SNPs were used for inferring haplotypes with SHAPEIT (19) followed by imputation of untyped SNPs with IMPUTE version 2 using as a reference all samples from phase 3 of the 1000 Genomes Project (from IMPUTE2 website, released December 2013) (20).…”
Section: Methodsmentioning
confidence: 99%
“…Both contribute to the Major Histocompatibility Complex Class 1 (MHC1) antigen processing pathway where ERAP1 plays a role in trimming peptides for optimal binding to MHC1 molecules, such as HLA-B27 (6,7). The ERAP1 association is restricted to HLA-B*27-positive cases or HLA-B*27-negative/HLA-B*40-positive cases (1,8,9). Several nonsynonymous ERAP1 single nucleotide polymorphisms (SNPs) (encoding amino acids M349V, K528R, D575N, R725Q, and Q730E) are associated with AS, including the protective "loss of function" variant 528R (10,11).…”
mentioning
confidence: 99%